End-users in recovery from substance use disorders as designers of Personas and digital games with therapeutic potential - Souza, Paula Maia de; Neris, Vânia Paula de Almeida; Proença, Fernando Roberto; Garcia, Franco Eusébio (Journal on Interactive Systems, 2022)
Thirty-five million people worldwide are affected by Substance Use Disorders (SUDs). Digital games can exert therapeutic effect in this domain and the development of these games by the end users themselves tends to potentiate the adherence and effectiveness of the games. Personas is a consolidated technique to support design solutions. There are studies in the literature that examine the creation of personas with the participation of health professionals. However, patients are generally just information providers and a more active participation is a desirable outcome to improve the design of digital systems for the healthcare domain. This paper investigates the co-creation of personas and digital games with therapeutic potential by patients recovering SUDs. Twenty-one patients, one healthcare professional and four computer science professionals took part in the workshops. In total, were created seven personas and four digital games with therapeutic potential. By conducting a qualitative analysis, we were able to determine eleven lessons learned from the process.